Actividad fititóxica y análisis del perfil químico por cromatografía de gases de aceites esenciales de piperáceaes potenciales herbicidas naturales 2020 - Caballero Ceferino, Henrry Denny (2022)
The annual application of herbicides in the world increases every year, due to the great losses of crops due to weeds, as an alternative to this, we have the use of agrochemicals, especially herbicides, which may be the only effective way to temporarily defend a weed crop. However, nowadays, dangerous herbicides are applied in the fields, causing harm to farmers, consumers and the environment. Due to this, the search for new alternatives is proposed, such as the identification of natural substances with allelopathic effects to obtain natural herbicides. Essential oils are a suitable type of allelochemicals to be used as bioherbicides due to their biodegradability, high structural diversity, and natural resistance to reducing weeds. The objective of this research is to search for phytotoxic potentials from the essential oils of plant species of the Piparaceae family. For the extraction of the ten (10) essential oils, the hydrodistillation method was used, the species are: P. coruscan Kunth, P. sancti-felicis trel, P. casapiense (Miq) C. DC, P. obliquum Ruiz & Pav, P. anonifolium (Kunth), P. tuberculatum Jacq, P. dumosum Rudge, P. reticulatum L, P. soledadense Trel y P. mituense Trel & Yunck. Essential oils were tested against the monocot Lolium perenne L. and the dicot Lactuca sativa F. As a result, it was observed that all Piper essential oils were active against L. perenne L, while only the essential oils of P. sancti-felicis trel, P. mituense Trel & Yunck, P. reticulatum L and P. casapiense (Miq) C. DC. were active against L. sativa F. In the analysis by gas chromatography pinned to masses of the essential oils that presented the best results of phytotoxic activity against L. perenne L and L. sativa F, were P. sancti-felicis (76,08%), P. mituense (51, 58%), P. reticulatum (14,99%), which have the phenylpropanoid apiol as the main compound and P. casapiense (22,64%) to the bicyclic compound [5,2,0] nonane, 2-methylene-4, 8,8-trimethyl-4-vinyl.